Comprehensive analysis Neddylation-related genes identified UBB as a prognostic biomarker for clear cell renal cell carcinoma - Shengren Cen; Yingpeng Li; Xinhao Xiong; Zihong Ma; Yongsheng Wang; Xingcheng Gao (Discover Oncology)
Abstract Neddylation, as a type of post-translational modification, plays a key role in cancer development. However, the biological characteristics and clinical prognosis value of Neddylation-related genes (NRGs) signatures in clear cell renal cell carcinoma (ccRCC) remain undetermined. Here, we identified two subtypes of NRGs in ccRCC based on TCGA data and constructed a NRGs risk signature (NRGS). Survival analysis, ROC curves, and nomograms showed that NRGS was an important predictor of prognosis in patients with clear cell renal cell carcinoma. We further revealed important correlations between NRGS and clinicopathological features, gene mutations, drug sensitivity, and immune cell infiltration. High NRGS indicates a poorer prognosis for kidney cancer, but higher remission rates with immunotherapy. Drug sensitivity also varies across risk groups. UBB was identified as a hub gene for NRGS and was downregulated in ccRCC, which is associated with poor prognosis. In conclusion, this study provides strategies for predicting prognosis and individualizing treatment for ccRCC.